2020
DOI: 10.1177/1948550620921619
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Temporal Exploration of the Relationship Between Wisdom-Related Cognitive Broadening and Subjective Well-Being: Evidence From a Cross-Validated National Longitudinal Study

Abstract: How do intraindividual changes in wisdom-related characteristics of cognitive broadening—open-minded reflection on challenging situations, consideration of change, and epistemic humility—relate to subjective well-being over time? To test this relationship, we performed cross-lagged panel analyses from three waves of the national U.S. sample taken across 20 years, utilizing a cross-validation approach: (i) conduct exploratory analyses on a random subset of data, (ii) preregister hypotheses and methods, and (iii… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…Further supplementary results from the Study 1 intervention show enhanced positive (rather than negative) feelings toward close others in conflict situations, as evidenced by a 1-month follow-up survey on social conflicts experienced by participants after the intervention. These results dovetail with emerging conclusions that wise reasoning provides prospective benefits for interpersonal feelings (Peetz & Grossmann, 2020) and well-being (Santos & Grossmann, 2020). 2…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Further supplementary results from the Study 1 intervention show enhanced positive (rather than negative) feelings toward close others in conflict situations, as evidenced by a 1-month follow-up survey on social conflicts experienced by participants after the intervention. These results dovetail with emerging conclusions that wise reasoning provides prospective benefits for interpersonal feelings (Peetz & Grossmann, 2020) and well-being (Santos & Grossmann, 2020). 2…”
Section: Discussionsupporting
confidence: 78%
“…Wisdom concerns a balanced, open approach to reasoning based on a desire to reconcile disparate viewpoints (Grossmann et al, 2020). It predicts a host of desirable outcomes, from harmonious interpersonal relationships (Brienza et al, 2018; Grossmann et al, 2017) to personal well-being (Santos & Grossmann, 2020). The current work showed that wisdom is not the purview of just a few fortunate individuals.…”
Section: Resultsmentioning
confidence: 99%
“…6.The original version of the AOMT by Stanovich and West (1997) consists of 41 items long, whereas the shortened version developed by Svedholm and Häkkinen and Lindeman includes 17 items. A slightly briefer version was used in the present study based on previous psychometric analyses showing that some low item-total correlations (e.g., Santos & Grossmann, 2021). …”
mentioning
confidence: 99%
“…To avoid the possible impacts of the biases in the demographic variables due to attrition on model estimates, the full information maximum likelihood (FIML) estimator was used in this study. FIML is an efficient technique for addressing missing values (Allison, 2003 ; Lee & Shi, 2021 ), and has been used in a variety of longitudinal studies with similar rates and amount of missing data (e.g., Liekefett et al, 2021 ; Luijten et al, 2022 ; Santos & Grossmann, 2021 ). FIML utilizes all available information to estimate model parameters, including information from cases with incomplete data (Enders & Bandalos, 2001 ; Ferro, 2014 ).…”
Section: Resultsmentioning
confidence: 99%